MONEY LAUNDERING ON THE BACKGROUND OF THE FINANCIAL CRISIS - A ROMANIAN REALITY - Iulian Gheorghe Ionita
The purpose of most illegal activities (especially those in the economic field), whether illegal as specific to organized crime networks (cigarette smuggling, alcohol; traffic of weapons, nuclear material, drugs, human beings; trade in protected species of animals and plants, with human tissues and organs; forgery of currency or other values etc.) or other illegal activities developed more or less in organized manner (such as embezzlement, corruption, tax evasion, fraud, informatics fraud), is to generate funds for the organized criminality group or individual that develops them. As these illegal activities generate substantial funds, the organized criminality group or individual (launderer) involved have to find a way to control these funds without attracting attention to the activity which generates them or to the persons concerned. Through the process of money laundering one tries and succeeds (in most cases) to hide the real origin and possession of these funds. In the context of the current financial crisis, the phenomenon of money laundering experiences an extension and a specialization without precedent. This situation demands a concerted reaction by the authorities who enforce the law in preventing and fighting money laundering and no only.underground economy, tax evasion, fraud, money laundering